IMPLEMENTASI INTERNATIONAL CONVENTION AGAINST DOPING IN SPORT DI INDONESIA (STUDI KASUS : PENYELENGGARAAN PON XVIII DI PROVINSI RIAU TAHUN 2012) - Ismul Al Azom; Tri Joko Waluyo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research explains implementation of the rules of the International Convention Against Doping in Sport in Indonesia (Case Study: Implementation of the Pekan Olahraga Nasional (PON) XVIII in Riau province in 2012). Doping is giving a drug or substance orally or parenterally to an athlete in a competition with the main objective to improve the performance of improperly. The use of doping in sport has been declared prohibited (illegal). In the 33rd session of the UNESCO (United Nations Educational, Scientific and Culture Organization) meeting on 19 October 2005 in Paris (France), the participating countries approved the contents of the international convention against doping in sport (International Convention Against Doping in Sport). The case of the use of doping can be found both on the national and international sporting events. One case of the use of doping in sport can be found in national sporting events namely PON XVIII in Riau Province in 2012. The final result of this research is the implementation of the International Convention Against Doping In Sport in Indonesia (Case Study: Implementation of the Pekan Olahraga Nasional (PON) XVIII in Riau Province in 2012) was conducted using precautions, doping control and sanctions for doping users in PON XVIII. The Government of Indonesia respect the the noble values of sport, Indonesia accepted the convention are realized with the establishment of Presidential Decree No. 101 of 2007 on the Ratification of the International Convention Against Doping in Sport, and the prohibition on the use of doping has been regulated in Article 85 of Law No. 3 of 2005 on Sports System..Keyword : Doping, International Convention, Implementation, Prevention, Doping Control , Giving sanctions.